2006
DOI: 10.1093/nar/gkl043
|View full text |Cite
|
Sign up to set email alerts
|

FOLD-RATE: prediction of protein folding rates from amino acid sequence

Abstract: We have developed a web server, FOLD-RATE, for predicting the folding rates of proteins from their amino acid sequences. The relationship between amino acid properties and protein folding rates has been systematically analyzed and a statistical method based on linear regression technique has been proposed for predicting the folding rate of proteins. We found that the classification of proteins into different structural classes shows an excellent correlation between amino acid properties and folding rates of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 28 publications
1
145
0
4
Order By: Relevance
“…Thus, inter-residue interactions have been one of the main focuses to understand the mechanisms of protein folding and stability [28][29][30][31][32][33][34]. Contact exploration in proteins could be of great interest from different perspectives, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inter-residue interactions have been one of the main focuses to understand the mechanisms of protein folding and stability [28][29][30][31][32][33][34]. Contact exploration in proteins could be of great interest from different perspectives, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of programs that predict the folding rate based on amino acid sequence integrated with other information have been published [8][9][10][11][12][13]. Recently, using Delaunay tessellation (DT) Ouyang and Liang [14] proposed a geometric contact (Nα) to replace the previous contact order.…”
mentioning
confidence: 99%
“…Plaxco and co-workers [119] showed that there is a high correlation between the folding rate and the structural properties of proteins, as defined by contact order CO, CO = 1 LN ∑ N ΔL ij , where L is the sequence length, N is the total number of inter-residue atomic contacts within a cutoff distance, ΔL ij is the sequence separation of contacting residues i and j. Interestingly, assessment of other protein folding rate determinants such as local and long-range contacts were found to perform equally well as the contact order [53]. Also, contact order is a geometric property which does not take into account the distribution and strength of the interactions on the rate [120].…”
Section: Protein Folding Kineticsmentioning
confidence: 98%
“…The Fold-Rate server (http://psfs.cbrc.jp/fold-rate/) [53] predicts rates of protein folding using the amino-acid sequence. The Parasol folding server (http://parasol.tamu.edu/groups/amatogroup/foldingserver) [54] predicts protein folding pathways using "probabilistic roadmaps"-based motion planning techniques.…”
Section: Studying Protein Foldingmentioning
confidence: 99%